contemporary Social Issues in Jhabvala’s “The Nature of Passion - P, Saranya Devi.; Keerthi, G. (International Journal of Psychosocial Rehabilitation, 2020)
The collision of Western ideals has been seen at many levels after Indian Independence. An epoch of technology and modern economy of science was being introduced. Science, education and in particular women were mounting. On the sociological level, certain radical changes of concept concerning the centre of power and influence in family and society were being introduced. A sense of alienation and unsettlement was a sequel to this transformation, for modernization set in motion a disturbance in the traditional pattern of Indian life without providing any viable alternatives.